2018
DOI: 10.1080/09638288.2018.1432705
|View full text |Cite
|
Sign up to set email alerts
|

Time burden of caring and depression among parents of individuals with cerebral palsy

Abstract: The frequency of depression among parents supporting individuals with CP exceeded preceding findings. Time pressure due to support appears to directly predict depression. Total time spent caring appears unrelated to depression. Implications for Rehabilitation It is necessary to prepare various community and family support systems in order to relieve parental caregivers' burden and exhaustion. Interventions should focus on parents with higher time pressure than parents with high caregiving time. Physical and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 20 publications
1
36
0
1
Order By: Relevance
“…In a study by Park and Nam, the parents spent about 14–15 h a day looking after a child with CP, without seeking support from other family members. The findings showed no effect of the time dedicated to care in the prevalence of depression, however increasing duration was associated with a greater risk of exceeding the threshold of depression [46]. The above results were confirmed by Sawyer et al who reported that time pressure significantly influenced the occurrence of depression among parents of children with CP [25]; likewise, Roxburgh established that time pressure predicted the occurrence of depression [47].…”
Section: Discussionmentioning
confidence: 80%
“…In a study by Park and Nam, the parents spent about 14–15 h a day looking after a child with CP, without seeking support from other family members. The findings showed no effect of the time dedicated to care in the prevalence of depression, however increasing duration was associated with a greater risk of exceeding the threshold of depression [46]. The above results were confirmed by Sawyer et al who reported that time pressure significantly influenced the occurrence of depression among parents of children with CP [25]; likewise, Roxburgh established that time pressure predicted the occurrence of depression [47].…”
Section: Discussionmentioning
confidence: 80%
“…Usual family life was disrupted by the need for intensive parent intervention in activities that are usually performed by a multidisciplinary team (rehabilitation professionals, teachers, etc.). The parents of children with disabilities already have to cope with the physical and mental health challenges associated with having a child with disabilities in normal times and are therefore particularly vulnerable during the pandemic [24] , [25] . The closure of schools and some specialized services and establishments in France during the lockdown increased the pressure on these parents, generating a high risk of parental exhaustion [25] , [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Although many caregivers cope with this new condition in the presence of CP, the lack of complete recovery of disorders leads to physical and psychological impact on caregivers. 18,19 Therefore, many scales have been developed where general physical and psychological health of children and their families are discussed, but in some of these scales 20 , family relationships at different levels, meal times and financial issues are not addressed or some of them included studies that were more specific (unemployed, single parents, etc. ), or have limited evaluations to reduce the number of questions.…”
Section: Discussionmentioning
confidence: 99%